Characterisation of Children's Head Motion for Magnetic Resonance Imaging With and Without General Anaesthesia - Eichhorn, Hannah; Vascan, Andreea-Veronica; Nørgaard, Martin; Ellegaard, Andreas H.; Slipsager, Jakob M.; Keller, Sune Høgild; Marner, Lisbeth; Ganz, Melanie (Frontiers in Radiology, 2021)
Head motion is one of the major reasons for artefacts in Magnetic Resonance Imaging (MRI), which is especially challenging for children who are often intimidated by the dimensions of the MR scanner. In order to optimise the MRI acquisition for children in the clinical setting, insights into children's motion patterns are essential. In this work, we analyse motion data from 61 pediatric patients. We compare structural MRI data of children imaged with and without general anaesthesia (GA), all scanned using the same hybrid PET/MR scanner. We analyse several metrics of motion based on the displacement relative to a reference, decompose the transformation matrix into translation and rotation, as well as investigate whether different regions in the brain are affected differently by the children's motion. Head motion for children without GA was significantly higher, with a median of the mean displacements of 2.19 ±0.93 mm (median ± standard deviation) during 41.7 ± 7.5 min scans; however, even anaesthetised children showed residual head motion (mean displacement of 1.12 ± 0.35 mm). For both patient groups translation along the z-axis (along the scanner bore) was significantly larger in absolute terms (GA / no GA: 0.87 ± 0.29 mm / 0.92 ± 0.49 mm) compared to the other directions. Considering directionality, both patient groups were moving in negative z-direction and thus, out of the scanner. The awake children additionally showed significantly more nodding rotation (0.33 ± 0.20°). In future studies as well as in the clinical setting, these predominant types of motion need to be taken into consideration to limit artefacts and reduce re-scans due to poor image quality. Registered at clinicaltrials.gov: NCT03402425.